1979
DOI: 10.1109/jqe.1979.1069893
|View full text |Cite
|
Sign up to set email alerts
|

Absorption coefficients and the temperature variation of the refractive index difference of nonlinear optical crystals

Abstract: Data on two parameters important for judging the deleterious effects of heating on the efficiency of nonlinear optical processes are presented. These parameters are absorption coefficients at 10.6 pm and the temperature variation of the refractive index difference for second harmonic generation of 5.3 um. The crystals examined are GaSe,T13AsSe3, AgGaSez, CdGeAsz, and Ag3AsS3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Since the themiooptic constants given by Bhar et al and the present authors exhibited no measurable temperature variation in the 2.052 -lO.591Oini range above room temperature, the alleviation of the thermal lensing observed below room temperature3 might be largely attributed to the rapid increase in the conductivity'4 rather than the decrease in dn I dT5 as the temperature is lowered. lfwe assume the thermal conductivity ofAgGaSe2 changes as K = 9.8 x 102 T'2 exp[O I T] (W/cm-K) (4) where 9 = 193K is the Debye temperature at 298K inferred from the calculated values of Abrahams and Hsu15, we found f= 41cm at 195K and f= 298cm at 77K, which are in close agreement with the experimental values given by Marquart et at3.…”
Section: Experiments and Discussionsupporting
confidence: 89%
“…Since the themiooptic constants given by Bhar et al and the present authors exhibited no measurable temperature variation in the 2.052 -lO.591Oini range above room temperature, the alleviation of the thermal lensing observed below room temperature3 might be largely attributed to the rapid increase in the conductivity'4 rather than the decrease in dn I dT5 as the temperature is lowered. lfwe assume the thermal conductivity ofAgGaSe2 changes as K = 9.8 x 102 T'2 exp[O I T] (W/cm-K) (4) where 9 = 193K is the Debye temperature at 298K inferred from the calculated values of Abrahams and Hsu15, we found f= 41cm at 195K and f= 298cm at 77K, which are in close agreement with the experimental values given by Marquart et at3.…”
Section: Experiments and Discussionsupporting
confidence: 89%
“…The latter finds a good fit to a special Sellmeier form, [8] observe, for p-type doped crystals, a residual shoulder on the intrinsic absorption edge for wavelengths up to 5.5 ~m, an absorption band near 5.5 p~m due to valence-band hole transitions in the p-type material that disappears in going from temperatures of 300 to 77 K, and three-phonon absorption at 13.5 /xm. In that regard, Barnes et al [23] measured the temperature dependence of the absorption coefficient at 10.6/zm and the index of refraction at 5.6/xm; however, their absorption coefficient was an order of magnitude larger than that determined by Iseler et al Mamedov and Osmanov [24] also observed the temperature dependence in p-type samples and an impurity absorption at 9.5 ~m. The shoulder at 5.5 tzm could present a difficulty for second-harmonic generation.…”
Section: Band Gap IIImentioning
confidence: 95%
“…The calculation of temperature distribution gives us an opportunity for determining wave-vector mismatching [19], investigating beam profile variations [20][21][22], measuring the weak absorption and defect identification of optical films [23], calculating the nonlinear conversion efficiency in second harmonic generation [7], analyzing the wavelength shift due to temperature rise in thin-film filters used for dense wavelength division multiplexing [24], measuring the thermal conductivity of laser crystals [25], and studying the thermo-optic properties of different materials [26]. As another example, the thermal models have also been used to study the diffraction images of thermal lenses [27].…”
Section: Introductionmentioning
confidence: 99%